2012
DOI: 10.1097/gme.0b013e31822a8d51
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular fat mass is positively associated with femoral neck bone mineral density in older women

Abstract: These data highlight that in older women, localization of FM is more important for bone mass than obesity per se or lean mass. AFM (subcutaneous adiposity) seems to exhibit an independent protective effect on BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Depot-specific fat has been known to play a different role in terms of obesity and metabolism. A previous study indicated that different fat depots might have distinct relationships with bone mass;22 Marques et al reported AFM had a positive association with femoral neck BMD in older women 23. Inconsistent with that, several studies stated AFM had no24 or a negative25 relationship with BMD.…”
Section: Discussionmentioning
confidence: 98%
“…Depot-specific fat has been known to play a different role in terms of obesity and metabolism. A previous study indicated that different fat depots might have distinct relationships with bone mass;22 Marques et al reported AFM had a positive association with femoral neck BMD in older women 23. Inconsistent with that, several studies stated AFM had no24 or a negative25 relationship with BMD.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, subcutaneous fat had a favorable effect on these bone parameters. A protective impact of subcutaneous fat on bone health (femoral neck BMD in elderly women) was also determined by Marquez et al [31]. On the other hand, Wang et al [32] failed to discern any detectable association between subcutaneous fat and lumbar spine BMD.…”
Section: Interactions Between Adipose Tissue and Bone Tissuementioning
confidence: 86%
“…Studies have yielded con icting results. Several studies 38,39 , such as the Older Afro-Caribbean Men study and another study on older women, have found that higher amounts of SAT are associated with higher BMD, suggesting a protective effect on bone health. Subcutaneous fat may help with bone strength in healthy young women according to research by Vicente Gilsanz et al 16 However, a research on Chinese women did not discover a connection between SAT and BMD.…”
Section: Discussionmentioning
confidence: 99%